Collisional and transport parameters of Cu in the warm dense matter regime calculated using the average atom model. (2nd November 2021) - Petrov, G M; Davidson, A
Abstract: Collisional and transport parameters for Cu are computed using the average atom model. Transition metals such as copper are difficult to model within the framework of the average atom model due to the presence of a narrow band of 3 d electrons that mix and hybridize with the broad 4 s band of nearly-free electrons. With electron temperature increasing, the 3 d electrons play a key role in the thermodynamics and transport properties of Cu (Lin et al 2008 Phys. Rev. B 77 075133), as well as the stability of the lattice (Loboda et al 2011 High Energy Density Phys. 7 361). In this work, the average atom model was used to track the average energy of the 3 d band and its evolution with electron temperature. At room temperature, its center is at ∼6 electron volts (eV), a few electron-volts below the Fermi energy, and with electron temperature increasing it sinks relative to it. At electron temperature of about 8 eV the 3 d electrons leave the conduction band and become bound. A long-standing problem related to the average ion charge observed by conduction band electrons is addressed and successfully resolved. A work-around has been found that predicts the correct average ion charge, Z ˉ, by formally introducing a third group of electrons: quasi-bound electrons. Benchmarking with published data is made that shows good agreement.